Paul McCartney [compact disc, unabridged] : a life - Carlin, Peter Ames (Tantor Audio, 2009)
Author Peter Ames Carlin presents an in-depth biography of the legendary musician and icon Paul McCartney, exploring his impact on music and culture, his personal triumphs and defeats, and his post-Beatles relationships with John Lennon, George Harrison, and Ringo Starr. The audiobook explores McCartney through the perspective of his lyrics, spanning his career from his years with the Beatles to his solo albums today.